Megachile rotundata (Fab.) as a potential agro-environmental conservation strategy for alfalfa seed production in Argentina - Renzi Pugni, Juan Pablo; Coito, Carlos; Reinoso, Omar Juan; Quintana, Matias; Garcia, Flavia Carina; Cantamutto, Miguel Angel (Wiley, 2021)
Alfalfa (Medicago sativa L. 1753) is one of the main forage crops of the world, and the availability of an adequate seed supply to farmers is one of the main concerns for the seed industry. The international alfalfa seed trade is widespread and several countries depend on imported seed. The continued importation of alfalfa seed carries a serious risk of unintentional introductions, such as contamination by genetically engineered (GE) alfalfa. We evaluated: (i) GE contamination in the main alfalfa seed production area of Argentina by analysing 263 conventional bulk seed lots (~900 tonnes) and feral populations (n = 49) over a 5-year period (2016–2021); and (ii) the location of alfalfa fields near natural vegetation formations as a pollination management strategy to increase the local seed production. Although GE alfalfa seed fields are prohibited, contamination was present in commercial seed lots (5.58% to 23.25%) and in feral alfalfa populations (8.16%). We did not observe an increase in the alfalfa seed yield in fields pollinated with honey bees (HB, Apis mellifera L., 1758) or located near natural vegetation formations when compared to fields pollinated by the alfalfa leafcutting bee (ALCB, Megachile rotundata Fabricius, 1793). In this study, use of the specialized pollinator ALCB was two to four times more effective than HB in terms of seed yield. Therefore, ALCB can reduce the risks of GE contamination by increasing the alfalfa yield in Argentina, which may then lead to a decrease in imported seed containing the potential contaminants. In addition, due to its specificity and small radial action, the ALCB could also drastically limit unintentional transgene diffusion. The reduction of seed importation will decrease the risk of worse biological or transgenic introductions of contaminants into national agroecosystems. Therefore, the use of ALCB as an input becomes a priority until new management practices are developed and adopted.